Perceived and Personal Mental Health Stigma in Latino and African American College Students - Stacie Craft DeFreitas; Travis Crone; Martha DeLeon; Anna Ajayi (Frontiers Media S.A., 2018)
Mental health stigma occurs when people have negative thoughts and beliefs of those with mental health illnesses or mental health treatment. Mental health stigma is related to an assortment of negative outcomes including discrimination in housing and employment, reduced usage of mental health services, and poor mental health outcomes. These implications may be particularly salient for ethnic minorities such as African Americans and Latinos who already suffer from other types of discrimination. This study examines perceived and personal mental health stigma in African American and Latino college students from a nontraditional university to help elucidate factors related to the development of mental health stigma. Students completed surveys concerning their stigma beliefs. African American students were found to have higher rates of mental health stigma than Latino students. Furthermore, anxiety about those with mental illness was related to greater mental health stigma for both groups. For African Americans, it was found that their perception of their ability to visibly identify those with mental illness was related to greater mental health stigma. These findings suggest that interventions to reduce mental health stigma in college students should target specific ethnic minority groups and focus on issues that are particularly salient to those communities.